Background of compilation of Vietnamese spelling dictionaries in the 20th century - Nguyen, Huyen Thi; Pham, Viet Hung (Institute of Education and Social Research, 2023)
Spelling has garnered much attention in Vietnam since as early as the introduction of the Latin-based script (Quốc ngữ). Alongside the study of Vietnamese spelling, efforts have been made to compile Vietnamese spelling dictionaries. The descriptive approach is the main research method used in this article. Specifically, we use this method to describe the macro and micro structures of Vietnamese spelling dictionaries. We go over the kind of entries and how they are arranged in each dictionary in terms of the macro structure. In the micro structure, we highlight the similarities and differences between different Vietnamese spelling dictionaries by describing the information provided for each entry. Additionally, statistical methods are used to collect information on Vietnamese spelling, classify specific spelling problems in Vietnamese, categorize Vietnamese spelling dictionaries, and choose representative dictionaries as the source of the article's material. To compare the macro and micro structures of these dictionaries, comparative analysis is also used. In the 20th century, Vietnam's lexicography developed vigorously and gained significant achievements, as evidenced by the emergence of numerous dictionaries in various genres, including spelling dictionaries. This article delves into the state of spelling dictionary compilation in the 20th century in Vietnam by examining and describing several works to explore the authors’ approaches and how they addressed spelling problems. Thereby, the article highlights the strengths and shortcomings in existing spelling dictionaries and suggests solutions with the goal of contributing to minimizing spelling errors.